Discrete time H∞ control - Limebeer, D; Green, M; Walker, D (IEEE, 1989)
A representation formula for all controllers for a given discrete-time system which satisfy an H∞ norm bound is given. The approach is based on the theory of linear quadratic difference games, with the time-varying, finite-horizon version of the problem being the main focus of attention. It is found that the controller representation formula can be specified in terms of a pair of discrete-time game-theoretic Riccati difference equations.